2014
DOI: 10.7600/jpfsm.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Interlimb neural interactions in the corticospinal pathways

Abstract: Corticospinal excitability is known to be modulated during voluntary muscle contraction of distal limbs. Although a large number of studies have demonstrated the variety of modulations in corticospinal excitability during distal limb movement, those interlimb neural interactions in corticospinal excitability have not been fully understood. Here, we mainly review previous studies that used transcranial magnetic stimulation (TMS) to report the modulation of corticospinal excitability during distal limb movement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 105 publications
(231 reference statements)
2
12
0
Order By: Relevance
“…First, before the relaxation (i.e., during contraction) of both the TA and SOL, we observed significant increases in MEP for both the ECR and FCR (Figure 3 ). This corresponds well with the results in previous studies which indicate that the facilitatory effect of the cortical mechanism on one limb during static contraction of other limbs displays a non-topographic characteristic (Tazoe et al, 2007 ; Chiou et al, 2013 ; Tazoe and Komiyama, 2014 ). The fact that the decrease in corticospinal excitability was observed in both ECR and FCR during TA relaxation indicated that the effect of foot relaxation spread to the forearm muscles, regardless of whether they were extensors or flexors (Figure 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…First, before the relaxation (i.e., during contraction) of both the TA and SOL, we observed significant increases in MEP for both the ECR and FCR (Figure 3 ). This corresponds well with the results in previous studies which indicate that the facilitatory effect of the cortical mechanism on one limb during static contraction of other limbs displays a non-topographic characteristic (Tazoe et al, 2007 ; Chiou et al, 2013 ; Tazoe and Komiyama, 2014 ). The fact that the decrease in corticospinal excitability was observed in both ECR and FCR during TA relaxation indicated that the effect of foot relaxation spread to the forearm muscles, regardless of whether they were extensors or flexors (Figure 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…Overall, these results imply that the remote effect results from both cortical and subcortical mechanisms; however, the relative contribution of each mechanism is not known (for a review, see ref. 26). …”
Section: Discussionmentioning
confidence: 99%
“…have reported that voluntary isometric knee extension facilitated wrist flexor MEP with linear relationship to knee extension force, and it remained unchanged even when knee extension force decreased due to central and peripheral muscle fatigue. It has been proposed that lack of reduction in MEP facilitation during the presence of fatigue may imply that the M1 is the source of neural generation of MEP facilitation in a remote segment26. Moreover, Tazoe et al 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticospinal remote facilitation has been studied extensively between upper-and lowerlimb muscles (Kawakita et al, 1991;Pereon et al, 1995;Tazoe and Komiyama, 2014) and this phenomenon is known as remote effect or crossed facilitation (Tazoe and Komiyama, 2014).…”
Section: Introductionmentioning
confidence: 99%